2020
DOI: 10.1101/2020.04.22.054114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diffusion-MRI-based regional cortical microstructure at birth for predicting neurodevelopmental outcomes of 2-year-olds

Abstract: Brain cerebral cortical architecture encoding regionally differential dendritic arborization and synaptic formation at birth underlies human behavior emergence at 2 years of age. Brain changes in 0-2 years are most dynamic across lifespan. Effective prediction of future behavior with brain microstructure at birth will reveal structural basis of behavioral emergence in typical development, and identify biomarkers for early detection and tailored intervention in atypical development. Here, we aimed to evaluate t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
(93 reference statements)
1
1
0
Order By: Relevance
“…In previous work with a smaller sample size and the inclusion of both term and preterm neonates, cortical FA at birth was found to significantly predict cognitive and language scores at two years using support vector regression (Ouyang et al 2020) with language-related features including the inferior frontal gyrus, insula and post-central gyrus, regions that were also identified in this current work. A longitudinal study of 33 term-born infants examined the relationship between deformationbased surface distance at neonatal timepoint and the Bayley-III scores at four different time points in the first two years of life (Spann et al 2014).…”
Section: Discussionsupporting
confidence: 59%
“…In previous work with a smaller sample size and the inclusion of both term and preterm neonates, cortical FA at birth was found to significantly predict cognitive and language scores at two years using support vector regression (Ouyang et al 2020) with language-related features including the inferior frontal gyrus, insula and post-central gyrus, regions that were also identified in this current work. A longitudinal study of 33 term-born infants examined the relationship between deformationbased surface distance at neonatal timepoint and the Bayley-III scores at four different time points in the first two years of life (Spann et al 2014).…”
Section: Discussionsupporting
confidence: 59%
“…Autism Spectrum Disorder participants also had higher FA and higher ADC values distributed throughout the cortical mantle. The cellular basis for these cortical findings is unclear, though early developmental studies in humans (Ouyang et al., 2019, 2020) and nonhuman primates (Jespersen, Leigland, Cornea, & Kroenke, 2012; Kroenke et al., 2007; McKinstry et al., 2002) have shown that FA in the cortical mantle declines during maturation as a consequence of increasing dendritic arborization, which directs diffusion of water within dendrites more randomly in space (Eaton‐Rosen et al., 2017; Hüppi et al., 1998; Neil et al., 1998) and thereby reduces FA. Therefore, higher cortical FA in ASD may represent reduced dendritic arborization and, as dendrites support synapse formation, it may represent reduced synaptic density as well.…”
Section: Discussionmentioning
confidence: 99%